PALMER, David Scott. Perú, The Authoritarian Tradition; Praeger Publishers,New York, 1980. 134 págs. - Klaiber, Jeffrey (1981)
Además también se encuentra la reseña de :PHILIP, George D.E. The Rise and Fall of the Peruvian Military Radicals, 1968-1976. The Athlone Press of the University of London, 1978. 1978. 178 págs.